Health issues in the curriculum of physical education in Sao Paulo: an integrative review - Barreta Garcia, Alessandro (2023)
The objective of this review was to perform an integrative review of the Brazilian literature on how health issues are included in the curriculum of physical education in the state of Sao Paulo. Data bases of LILACS, Digital library of thesis in Brazil were reviewed. We selected studies that included health issues divided into three categories; superficial description of the topic, ignored health issues and detailed description of health issues. We identified 439 sources including 24 studies. In eleven of them a superficial cover was detected, four covered the issues in depth and nine ignored the issue. Two studies were identified in the 1970-1989 and 1990-1999 periods. Just one of them centered in health topics. Authors who covered health issues superficially between 2000-2014 opposed to traditional curriculum. Those who covered in more detail health topics talk about the importance of including these concepts in the schools.